2023
DOI: 10.3390/agronomy13061553
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bacillus velezensis with Antibacterial Activity and Its Inhibitory Effect on Gray Mold Germ

Abstract: The present study provides a comprehensive overview of the Bacillus velezensis strain Htq6, and its potential applications in plant disease control. Htq6 is an endophytic bacterium derived from walnut, which was found to possess a strong inhibitory effect on a wide range of plant pathogenic microorganisms and was identified as a good plant disease control agent. The entire genome of the Bacillus velezensis Htq6 was sequenced, and a comparative genomic analysis was conducted with various Bacillus species in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Li et al [ 30 ] found that LAB can produce β-glucosidase during the metabolic process, and the magnitude of its activity is the main factor determining the conversion of saponins into rare saponins. β-Glucosidase can also utilize substrates to generate other active substances, thereby enhancing the antioxidant activity of the fermentation broth [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [ 30 ] found that LAB can produce β-glucosidase during the metabolic process, and the magnitude of its activity is the main factor determining the conversion of saponins into rare saponins. β-Glucosidase can also utilize substrates to generate other active substances, thereby enhancing the antioxidant activity of the fermentation broth [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [30] found that LAB can produce β-glucosidase during the metabolic process, and the magnitude of its activity is the main factor determining the conversion of saponins Li et al [30] found that LAB can produce β-glucosidase during the metabolic process, and the magnitude of its activity is the main factor determining the conversion of saponins into rare saponins. β-Glucosidase can also utilize substrates to generate other active substances, thereby enhancing the antioxidant activity of the fermentation broth [31].…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…Many species exhibit a wide range of physiological traits, which enable their survival in a diverse natural environment ( 1 ). Bacillus velezensis was formerly classified as strains of Bacillus amyloliquefaciens but reclassified based on genomic analysis ( 2 , 3 ). Comparative genomics and DNA-DNA relatedness calculations had, however, showed that B. velezensis was taxonomically distinct from B. amyloliquefaciens ( 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…The prevalence of vegetable fungal diseases is on the rise, and gray mold of tomato caused by Botrytis cinerea is a serious threat to crop yield and quality [2,3]. Botrytis cinerea causes yield loss of more than 20% and economic loss of tens of billions of yuan each year [4]. It poses a significant threat to the productivity of tomato crops by infiltrating multiple plant components, including stems, leaves, and fruits, thereby compromising food safety [5].…”
Section: Introductionmentioning
confidence: 99%